The role of produce surface topography on foodborne virus inactivation on polydimethylsiloxane topomimetic artificial leaf surfaces and fresh leafy green surfaces - Lightbown, Ashlyn; DiCaprio, Erin (Frontiers in Plant Science, 2025)
Fresh leafy greens are a commodity known for high susceptibility to human norovirus contamination under pre- and post-harvesting conditions. However, the role of the leafy green surface topography on the attachment and removal of this pathogen is poorly understood. Romaine lettuce and spinach leaves from multiple plant stages of growth presenting variable microscale surface topographies were evaluated through the recovery of a human norovirus surrogate, Tulane virus (TV), and the impact on sanitizer inactivation. A previously developed model system using polydimethylsiloxane (PDMS) topomimetic artificial leaf surfaces (“replicasts”) was also used to elucidate the impact of produce surface topography on virus adhesion and inactivation, and to validate the use of this tool for produce safety-related studies. Overall, the leaf age or axis (adaxial or abaxial surface inoculated) did not influence the recovery of TV from romaine lettuce and spinach control samples (fresh or replicast). However, when evaluating the efficacy of two sanitizers commonly used in post-harvest wash water for leafy greens (sodium hypochlorite and peracetic acid), spinach leaf age impacted efficacy. Younger spinach leaves (15-day) had significantly higher inactivation (lower recovery) of infectious TV when treated with sodium hypochlorite compared to older leaves (45-day). The leaf axis did not impact TV inactivation in spinach. There was no influence of leaf age or axis on the inactivation of TV in romaine lettuce. Through modulation of replicast surface hydrophobicity utilizing surfactant addition to TV inoculum, we were able to mimic plant leaf hydrophobicity. It was found that romaine replicasts demonstrated comparable virus recovery to fresh plant tissue with 0.05% Tween 20 addition to TV inoculum. These data demonstrate that variations in microscale topography of spinach based on leaf age can influence the efficacy of sanitizers against TV, however this influence was not observed for romaine lettuce of either age or axis. Additionally, the data generated utilizing PDMS replicasts indicates these can be useful tools for studying foodborne virus recovery and inactivation in leafy greens.